Futures Price Dynamics of European Carbon Emission Certificates - An Econometric Analysis - Ye, Jing (2010)
Carbon emission allowances are traded with increasing liquidity and the carbon emission market has grown rapidly since the Kyoto Protocol launched in 2005. Besides the spot market, the trading of derivatives investment instruments with underlying assets of carbon emission certificates, especially futures contracts, also experienced the high speed expansion. This dissertation focuses on the futures contracts prices dynamics of carbon emission certificates, and develops the different valuation models of EUA intra-phase and inter-phase futures contracts, respectively. The issues of convenience yields, ARCH effect, and asymmetric effects on prices of good news and bad news that are suggested by the empirical analysis are also addressed in this dissertation.